2005
DOI: 10.1089/thy.2005.15.1253
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism Might Be Related to Breast Cancer in Post-Menopausal Women

Abstract: Hypothyroidism might be related to breast cancer in post-menopausal womenKuijpens, J.L.; Nyklicek, Ivan; Louwman, W.J.; Weetman, A.P.; Pop, Victor; Coebergh, J.W.W. Published in: Thyroid Document version:Publisher's PDF, also known as Version of record General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(163 citation statements)
references
References 31 publications
(45 reference statements)
6
142
0
5
Order By: Relevance
“…Nevertheless, other studies have demonstrated a higher (8,21,22) or a lower incidence of thyroid disease in BC cases (23). Hashimoto's disease, with or without positive thyroid antibodies (TPO-Abs and Tg-Abs), has been shown to be associated with an increased risk of BC (8,9,(24)(25)(26)(27) and, according to some studies, with a better prognosis and increased disease-free survival in BC cases (16,28).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, other studies have demonstrated a higher (8,21,22) or a lower incidence of thyroid disease in BC cases (23). Hashimoto's disease, with or without positive thyroid antibodies (TPO-Abs and Tg-Abs), has been shown to be associated with an increased risk of BC (8,9,(24)(25)(26)(27) and, according to some studies, with a better prognosis and increased disease-free survival in BC cases (16,28).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, subgroup analysis showed that BC patients in Europe have higher serum FT 3 levels than the control group, although no significant differences in FT 4 and TSH levels were observed. Hellevik et al reported that low levels of FT 4 and high levels of TSH were associated with an increased risk of BC (Kuijpens et al, 2005). However, another study found no association between TSH levels and breast cancer risk (Hellevik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Full--text ar+cles assessed for eligibility (n =21) Figure.1) (Turken et al, 2003;Cengiz et al, 2004;Kuijpens et al, 2005;Saraiva et al, 2005;Giustarini et al, 2006;Ditsch et al, 2010;Ali et al, 2011;Szychta et al, 2013) . Tables 1 and 2 show the characteristics and data of all 8 studies included in our analysis.…”
Section: Iden0fica0onmentioning
confidence: 99%
See 1 more Smart Citation
“…A relationship between the effects of immune system, autoimmune and chronic inflammatory disease and malignancies, like breast cancer is suggested in some recent studies (6). Some studies show a relationship between hypothyroidism including autoimmune types with increased risk of breast cancer (7,8). There are also some researches that indicate an increased risk of cancers such as breast cancer in patients with multiple sclerosis (9,10).…”
Section: Introductionmentioning
confidence: 99%